2021
DOI: 10.1007/s12018-021-09278-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxidative Stress on Bone Remodeling in Periprosthetic Osteolysis

Abstract: The success of implant performance and arthroplasty is based on several factors, including oxidative stress-induced osteolysis. Oxidative stress is a key factor of the inflammatory response. Implant biomaterials can release wear particles which may elicit adverse reactions in patients, such as local inflammatory response leading to tissue damage, which eventually results in loosening of the implant. Wear debris undergo phagocytosis by macrophages, inducing a low-grade chronic inflammation and reactive oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 126 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…There is, however, surprisingly limited knowledge on the influence of the biomechanical environment in the bone and bone-implant interface on the redox balance, with some of the information available based on maxillofacial implantology focusing on the effects of the implant itself. It is recognized that ROS boost the inflammatory response and cause both RANKL-induced osteoclastogenesis and osteoblast apoptosis, leading to periprosthetic osteolysis aseptic loosening, the most frequent cause of implant failure ( Borys et al, 2018 ; Ozawa et al, 2020 ; Galliera et al, 2021 ). Bone unloading such as observed in disuse and microgravity conditions leads to decreased bone mass and quality, through redox-mediated pathways.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, surprisingly limited knowledge on the influence of the biomechanical environment in the bone and bone-implant interface on the redox balance, with some of the information available based on maxillofacial implantology focusing on the effects of the implant itself. It is recognized that ROS boost the inflammatory response and cause both RANKL-induced osteoclastogenesis and osteoblast apoptosis, leading to periprosthetic osteolysis aseptic loosening, the most frequent cause of implant failure ( Borys et al, 2018 ; Ozawa et al, 2020 ; Galliera et al, 2021 ). Bone unloading such as observed in disuse and microgravity conditions leads to decreased bone mass and quality, through redox-mediated pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to reduce lipid peroxidation in the brain of D-galactose-induced aged rats 50 . It has been reported that oxidative stress and inflammation stimulate osteoclast differentiation, resulting in increased bone resorption 51 , 52 , implying that the reduction in Oc.S/BS in the current study could be due to the antioxidant and anti-inflammatory activity of KSLP. For bone remodelling markers, significant differences between KSLP groups and other groups prior to treatment were noted.…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrollable bone-related complications like osteoporosis, osteoarthritis, rheumatoid arthritis, bone cancer, and many other bone disorders are instigated by an interruption in these pathways (Barnsley et al, 2021). Although oxidative strain has been related to the development of osteoblasts, vital for bone health, extreme oxidative strain stimulates osteoclast discrepancy while conquering osteoblast genesis (Galliera et al, 2021). Correspondingly, inflammation, which is essential for the remodeling of bones, inclines the bone to compulsive stress and becomes chronic, as observed in postmenopausal women and older men (Xie et al, 2019) because of lesser total antioxidant capability and greater inflammation as compared to healthy people (Epsley et al, 2021).…”
Section: Bone and Joint Healthmentioning
confidence: 99%